(untitled) (Singaporean Journal of Business Economics and Management, 2015)
Yet, no comprehensive model of the evolution of systems thinking may be found in the literature despite its necessity. System thinking is unclear, but based on some ideas it is conceptual, and it seems a quality expression, so we need to a suitable tool for measuring of systems thinking. There are very limited researches Evaluate systems thinking in management science. This paper measures system thinking by Balance Score Card (BSC) for the Behnoosh corporate in Iran. This article uses following structure based on four perspective of BSC (Learning and Growth, Internal Processes, clients, and Financial). First, some factors in vertical linkages within the systems measured. Thereafter, other factors on a horizontal basis are measured in the connections from suppliers to buyers. Finally, relationship between vertical linkages and horizontal connections measured. The results of this study seem to suggest that system thinking is existed in Behnoosh, because implemented vertical linkages and horizontal connections in four perspective of BSC, and there is meaningful relationship between them. At the end of the article, there are some implications for managers and some suggestions for the future studies.